STUDY OF SOIL CHARACTERISTICS AND LAND USES WITH REFERENCE TO PLANING AND DEVELOPMENT OF MICRO WATERSHEDS IN THE UPPER DAMODAR VALLEY CATCHMENT A case study - Mondal, S.K.; Sarkar, A.K.; Misra, K. (Journal of Soil and Water Conservation, 2022)
The percent paper duty with the identification of three soil series Atia, Harian, and Bhuswa which were described and mapped. Harina and Bhuswa soils have loamy sand and silty clay loam in the epipedons followed by silt loam to clay in the sub soil horizons with illuvial argilans. The soils have been placed under alfisols. They are very gently to moderately slopping, well drained to moderately well drained, moderately to serve eroded, acidic to neutral in reaction, moderate to low in water holding capacity The soils in general have been placed under land capability classes II and III with sub classes indicating the prominence of problems to be tackled. More than 70% of the soils are fit for cultivation with soil conservation measures like contour building graded bunding, strip cropping or intercropping with legumes. In some areas waterharvesting structures, silt detension dams and grassing of water ways will be useful to arrest high silt flow to the reservoir. The deep and narrow gullies are absolutely recommended for afforestation. Some of the gullies mainly small and medium can be reclaimed for paddy cultivation by gully plugging method.